Pedagogical Foundations For Creating a Developmental Environment In Preschool Educational Institutions - Nematovna, Begmatova (Indonesian Journal Publisher, 2025)
The formation of a developmental environment in preschool educational institutions directly influences children's intellectual, social, and emotional development. This article explores the pedagogical foundations of creating a developmental environment, including activity-based teaching, individualized learning, support for social and emotional development, and the significance of an integrative approach. Additionally, it highlights the importance of principles such as play-based learning, experience-based education, and socialization for preschool-aged children. Research findings indicate that a developmental environment established based on modern pedagogical approaches fosters children's independent thinking, communication skills, and creative activities.